A systematic review on the surgical outcome of preauricular sinus excision techniques. (4th January 2016) - Bruijnzeel, Hanneke; van den Aardweg, Maaike T.; Grolman, Wilko; Stegeman, Inge; van der Veen, Erwin L.
Abstract : Objectives/Hypothesis: Preauricular sinuses are benign congenital malformations of preauricular soft tissues. Complete excision using either sinectomy or supra‐auricular approach is advised to prevent recurrence. Reported recurrence varies between 0 and 42%. We evaluated which surgical technique resulted in lowest complication and recurrence rates. Study Design: PubMed, Embase, Scopus, Web of Science. Methods: Two authors appraised studies on directness of evidence and risk of bias. Original data were extracted and pooled when I 2 was smaller than 50%. Results are reported according to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses statement. Results: Fourteen high directness of evidence studies were included. Reported complication rates were similar: sinectomy [0–31.4%] and supra‐auricular approach (SAA) [0–18.2%]. Pooled recurrence rates showed that sinectomy resulted in significantly ( P = .04) more recurrence 5.5% (95% confidence interval [CI] 3.6–8.3%) than SAA 2.2% (95% CI 0.7–7.0). Sinectomy using the microscope resulted in the lowest sinectomy recurrence rates (1.9%). SAA in combination with a Penrose drain resulted in 0% recurrence in revision cases. Drain use resulted in the lowest SAA recurrence rates; however, drain application was not advised due to higher complication rates (frequent wound infection [ P = .003] and more [ P = .002] and longer [ P = .001] compression dressing use). Conclusion: SAA could be the preferable technique for preauricular sinus removal. If despite evidence, sinectomy is elected over SAA, microscope use can further decrease recurrence rates comparable to SAA levels. Level of included evidence (Ib–IV) indicates the need for a prospective study comparing surgical outcomes between techniques. Laryngoscope, 126:1535–1544, 2016